Helicobacter pylori and extragastric diseases. (September 2016) - Goni, Elisabetta; Franceschi, Francesco
Abstract: During the past year, many articles were published on the extragastric diseases related to Helicobacter pylori infection. This supports the theory that some microorganisms may cause diseases even far from the primary site of infection by interfering with different biologic processes. The role of H. pylori on idiopathic thrombocytopenic purpura, sideropenica anemia, and vitamin B12 deficiency is well known. On the other hand, there is a growing interest in the bacterium's association with cardiovascular, neurologic, hematologic, dermatologic, head and neck, and uro‐gynecologic diseases, as well as diabetes mellitus and metabolic syndrome, with very promising results. This review has been aimed at summarizing the results of the most relevant studies published over the last year on this fascinating topic.